The boat rocker : a novel - Jin, Ha, 1956- (Pantheon Books, 2016)
"New York, 2005. Chinese expatriate Feng Danlin is a fiercely principled reporter at a small news agency that produces a website read by Chinese all over the world. Danlin's explosive exposés have made him legendary among readers--and feared by Communist officials. But his newest assignment may be his undoing: investigating his ex-wife, Yan Haili, an unscrupulous novelist who has willingly become a pawn of the Chinese government in order to realize her dreams of literary stardom. Hanli's scheme infuriates Danlin both morally and personally--he will do whatever it takes to expose her as a fraud. But in outing Haili, he is also provoking her powerful political allies, and he will need to draw on all of his journalistic cunning to come out of this investigation with his career--and his life--still intact. A brilliant, darkly funny story of corruption, integrity, and the power of the pen, The Boat Rocker is a tour de force"--